Cryogenic Target System for Hydrogen Layering. (1st February 2016) - Parham, T.; Kozioziemski, B.; Atkinson, D.; Baisden, P.; Bertolini, L.; Boehm, K.; Chernov, A.; Coffee, K.; Coffield, F.; Dylla-Spears, R.; Edwards, O.; Fair, J.; et al.
Abstract: A cryogenic target positioning system was designed and installed on the National Ignition Facility (NIF) target chamber. This instrument incorporates the ability to fill, form, and characterize the NIF targets with hydrogen isotopes needed for ignition experiments inside the NIF target bay then transport and position them in the target chamber. This effort brought to fruition years of research in growing and metrologizing high-quality hydrogen fuel layers and landed it in an especially demanding operations environment in the NIF facility. D-T (deuterium-tritium) layers for NIF ignition experiments have extremely tight specifications and must be grown in a very highly constrained environment: a NIF ignition target inside a cryogenic target positioner inside the NIF target bay. Exquisite control of temperature, pressure, contaminant level, and thermal uniformity are necessary throughout seed formation and layer growth to create an essentially-groove-free single crystal layer. The team developed processes, procedures, software, and metrology techniques to form and qualify solid layers of hydrogen isotopes at a quality level and yield needed to support the National Ignition Campaign experimental program. The team has grown over 220 layers in NIF, and 52 have been shot to date.